EarthTones: Chemical Sensing Powders to Detect and Display Environmental Hazards through Color Variation - Cindy Kao; Nguyen, Bichlien; Roseway, Asta; Michael Dickey (CHI, May 06-11, 2017, 2017)
We present EarthTones, cosmetic-inspired wearable chemical sensing powders to detect and display harmful environmental factors through color change. We seek to create an analog display experience through chemical reactions that overcome current constraints of rigid, battery-laden wearable displays. We designed three unique chemical changing powders to reflect elevated levels of carbon monoxide (CO), ultraviolet (UV) rays, and ozone (O3). The powders achieve color changes distinguishable to the human eye, while maintaining an aesthetic appeal to the wearer. Our technical evaluations confirmed the performance of the powders to detect and display elevated levels. An 18- person exploratory study provided insight to the perceptions, possibilities, and challenges of a powder form factor for wearable environmental visualization. Through this paper, we intend to enable the use of colorimetric chemical displays for HCI researchers and designers. More generally, we seek to encourage the research and use of chemical-based sensors and interdisciplinary research in HCI.